STRATEGIES FOR DEEP LEARNING: ECONOMIC MANAGEMENT SCIENCES TEACHERS' VIEWS AND PRACTICES IN JOHANNESBURG (Proceedings of the International Conference on Education, 2025)
This study explores Economic and Management Sciences (EMS) teachers' perspectives on deep learning and how EMS classrooms create constructivist, student- centered learning opportunities. Grounded in cognitive and constructivist theoretical frameworks, the study examines how teachers' experiences, beliefs, and attitudes shape their instructional practices in fostering deep learning, emphasising content mastery, critical thinking, and real-world application. While cognitive theory explains how teachers' prior knowledge influences their teaching strategies, constructivist theory highlights how learners construct knowledge through engagement and problem-solving. A qualitative research approach was employed, utilising semi-structured telephone interviews with six purposively sampled EMS teachers from four public schools in Gauteng, South Africa. Purposive sampling ensured participants had at least five years of EMS teaching experience, providing rich insights into deep learning practices. Interview questions focused on teachers' understanding of deep learning, instructional strategies, and challenges in EMS classrooms. Narrative data analysis identified themes through coding and clustering of recurring insights, centring teachers' voices and lived experiences. Findings reveal that teachers perceive deep learning as fostering content mastery beyond memorisation, enabling learners to apply knowledge across contexts. However, limited resources, time constraints, and lack of EMS teacher training hinder its effectiveness. Strategies supporting deep learning include problem-based learning, critical thinking, collaboration, ICT integration, and mini-enterprise activities, aligning with constructivist principles. Despite a small sample size limiting generalizability, the in-depth narratives offer valuable insights. Telephone interviews addressed geographical constraints and teacher availability, ensuring data depth and accessibility. This study contributes to commerce education research by highlighting how a blended cognitive-constructivist approach can enhance EMS curriculum design, equipping learners for the dynamic business environment.
Keywords: deep learning; EMS pedagogy; cognitive theory; constructivist learning; teacher education; entrepreneurship education